Tertiary nutrient removal from wastewater by immobilised microalgae: impact of wastewater nutrient characteristics and hydraulic retention time (HRT) - Whitton, Rachel; Santinelli, Martina; Pidou, Marc; Ometto, Francesco; Henderson, Rita; Roddick, Felicity; Jarvis, Peter; Villa, Raffaella; Jefferson, Bruce (IWA Publishing, 2018)
Immobilising microalgal cells has been proposed as a process solution to overcome the barriers associated with the implementation of microalgae for wastewater remediation. This work evaluated the performance and remediation mechanisms of immobilised microalgae for continuous wastewater treatment under varying hydraulic retention times (HRT). Three domestic secondary wastewaters with differing concentrations of orthophosphate (PO4-P), ammonium (NH4-N) and nitrate (NO3-N) were treated by Scenedesmus obliquus immobilised within 2% calcium alginate. Trials were run in continuous operation at HRTs of 3, 6, 12 and 20 h. Removal rates for PO4-P improved with increasing HRT, with minimum residual concentrations of 0.3–3.1 mg·L−1 observed at 3 h and 0.01–0.2 mg·L−1 at 20 h. Ammonium remediation was not linked to HRT or NH4+ concentration with minimum residual concentrations of <0.001 mg·L−1. Reduction in NO3-N improved with increasing HRT, with minimum residual concentrations of ≤19.3 at 3 h and ≤0.4 mg·L−1 at 20 h. Remediation was achieved through a combination of mechanisms including biological uptake and precipitation as a by-product of photosynthesis and nutrient metabolism. As such, immobilised microalgae have been proven to be an effective alternative solution for PO43− and NH4+ remediation of wastewater effluents at HRTs of 6–12 h.
Keywords: hydraulic retention time; immobilised microalgae; wastewater